1994
DOI: 10.1111/j.1365-2958.1994.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Folate responsiveness during growth and development of Dictyostelium: separate but related pathways control chemotaxis and gene regulation

Abstract: Folate-controlled gene expression and chemotaxis have been examined in Dictyostelium wild-type and mutant strains. We show that regulation of the discoidin genes is sensitive to folate in growing cells as well as in suspension development. The signal is transferred via the N10-methylfolate-sensitive folate receptor sites, which also appear to confer the chemotactic response. The strain HG5145 has previously been isolated as a mutant that does not display chemotactic movement towards folate. Nevertheless, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Bacteria secrete folic acid, and this molecule chemotactically attracts vegetative amoebae, resulting in successful predation and feeding (1). The role of RasG and RasC in folate chemotaxis was determined by measuring the movement of cells toward a folate filled micropipette.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria secrete folic acid, and this molecule chemotactically attracts vegetative amoebae, resulting in successful predation and feeding (1). The role of RasG and RasC in folate chemotaxis was determined by measuring the movement of cells toward a folate filled micropipette.…”
Section: Resultsmentioning
confidence: 99%
“…To understand its possible role in these processes, attempts were made to overexpress the gene. Since preliminary experiments, using a constitutive actin 15 promoter, indicated that overexpression of the rasG gene might be toxic to the cell, the gene was cloned downstream of the folate-repressible discoidin (dis1␥) promoter in the vector pVEII (4,5), and the resulting construct, pVEII-rasG, was used to transform Ax-2 cells. Transformants were selected in the presence of 1 mM folate to repress the discoidin promoter.…”
Section: Resultsmentioning
confidence: 99%
“…This low level expression of rasG-G12T had no effect on growth but caused impaired aggregation under certain developmental conditions (40). In the study reported here, we have successfully overexpressed the rasG gene by using the folate-repressible discoidin promoter (4,5) and have determined the effects of overexpression on growth and differentiation.…”
mentioning
confidence: 99%
“…Above a threshold level of the PSF:bacteria ratio (approximately three generations before the onset of starvation), low-level discoidin expression is initiated (Rathi et al, 1991). Folate represses discoidin expression when added to axenically growing cells (Blusch and Nellen, 1994). Similarly, autoclaved bacteria can repress discoidin (Burdine and Clarke, 1995).…”
Section: Introductionmentioning
confidence: 99%